Cartilage Tissue Formation from Dedifferentiated Chondrocytes by Codelivery of BMP-2 and SOX-9 Genes Encoding Bicistronic Vector. Issue 9 (September 2013) - Cha, Byung-Hyun; Kim, Jae-Hwan; Kang, Sun-Woong; Do, Hyun-Jin; Jang, Ju-Woong; Choi, Yon Rak; Park, Hansoo; Kim, Byung-Soo; Lee, Soo-Hong
Articular cartilage, when damaged by degenerative disease or trauma, has limited ability for self-repair. Recently, many trials have demonstrated that gene therapy combined with tissue engineering techniques would be a promising approach for cartilage regeneration. Bone morphogenetic protein 2 (BMP-2) is an important signal for upregulation of osteogenesis and chondrogenesis of stem cells. Sex-determining region Y box gene 9 (SOX-9) has also been reported as one of the key transcription factors for chondrogenesis. We hypothesized that codelivery of BMP-2 and SOX-9 genes would result in improved efficiency of recovery of normal chondrogenic properties in dedifferentiated chondrocytes. To this aim, we constructed a bicistronic vector encoding the BMP-2 and SOX-9 genes linked to the "self-cleaving" 2A peptide sequence. After gene delivery to dedifferentiated chondrocytes using a microporator transfection system, we confirmed over 65% delivery efficiency of the BMP-2 and SOX-9 genes. According to RT-PCR analysis and Alcian blue staining, simultaneous delivery of BMP-2/SOX-9 resulted in significantly increased expression of chondrogenesis-related markers (type II collagen and aggrecan) and GAG matrix formation compared with individual delivery of the BMP-2 or SOX-9 gene. Six weeks after in vivo transplantation, BMP-2/SOX-9 genes also showed a significant increase in cartilage formation compared with the BMP-2 or SOX-9 gene. These results demonstrate that codelivery of two chondrogenic lineage-determining genes can enhance normal chondrogenic properties of dedifferentiated chondrocytes followed by improved cartilage formation.